Homemcavalo: uma etnografia dos carroceiros de Belo Horizonte - Nian Pissolati Lopes (2013)
This work aims to describe and discuss the way of life of the horse carters who work and mostly live on the Far East region of Belo Horizonte. The analysis is based on three relational axis intrinsic to carters life human-animal interaction; spatiotemporal relation with the city; relationship with others social agents. The work also takes part in the field of anthropology of the image, since it uses the photographic device as a methodological tool for interaction and also as a ethnographic and analytical instrument.